An integrated computer package for productivity, cost control and schedule control systems (INPROMA) / Noorman Nordin - Nordin, Noorman (1993)
Most project analysist have the dream of integrating cost, productivity and schedule function. In practice it is very difficult to achieve the same. Often it is observed CPM engineers producing schedules and cost engineers working on budget and completion status, with little correlation between this three function. This project attempt to developed a software package which will make the three function integrate or related each others.